Some aspects of physiological studies of two reef building corals in the red sea - Yahya AM Floos; Abdulmohsin AAl-Sofyani (Open Journal of Biological Sciences - Peertechz Publications, 2023)
Some aspects of the physiology of the corals Seriatopora hystrix and Lobophyllia corymbosa described in this paper. At the study site, the lowest mean of seawater temperature is 27.42 °C and 27.17 °C at 5m and 10m depths respectively during winter, while the maximum mean of seawater temperature was 32.67 °C and 31.17 °C in 5 m and 10 m depths respectively during summer. L. corymbosa, had a lower number of zooxanthellae 0.05×105 , 0.43×105 , 0.06×105 and 0.46×105 mg-1 dry tissue weight than S. hystrix 0.19 ×105 , 5.1 ×105 , 0.27×105 and 9.59×105 mg-1 dry tissue weight in two season and two depths respectively. The mean respiration rate of whole colonies of S. hystrix was higher than that of L. corymbosa at the same depths both in summer and winter. The mean dark respiration rate decreases with increasing depths. The mean photosynthesis vs irradiance curves of S. hystrix and L. corymbosa were plotted to the hyperbolic tangent function (Chalker,1981) for summer and winter season. The growth rate was linear during each period of measurement during summer, the highest mean daily skeletal growth rate of S. hystrix was 2.3 ± 1.3 (20) mg.skel.d-1 in 10m depth and it was 1.6 ± 0.5 (21) mg .skel.d-1 at 5m depth. Whilst during winter, the lowest was 1.9 ± 0.96 (20) mg .skel. d-1 at 10m and also lowest (1.5 ± 0.7 (20) mg .skel. d-1) at 5m depth. The growth rate of the two species was lower in the winter than in summer.